2021
DOI: 10.1111/jcpp.13477
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from maternal shyness to adolescent social anxiety

Abstract: Background: Social anxiety is amongst the most prevalent adolescent mental health problems; however, it is often unrecognized due to its comorbidity with other anxiety problems such as generalized anxiety. Thus, understanding the unique developmental pathways to social anxiety is critical for improving its prevention. We examined the pathway from maternal shyness, when children were 4 years old, to adolescents' social anxiety at age 15 through social wariness at age 7. We hypothesized that childhood social war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Similarly, Zeytinoglu et al. (2022) found that social wariness to unfamiliar peers at 7 years specifically predicted social anxiety but not generalized anxiety at 15 years. Together, these findings suggest that there is a unique link between inhibited behaviors in social contexts and subsequent social anxiety.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Zeytinoglu et al. (2022) found that social wariness to unfamiliar peers at 7 years specifically predicted social anxiety but not generalized anxiety at 15 years. Together, these findings suggest that there is a unique link between inhibited behaviors in social contexts and subsequent social anxiety.…”
Section: Discussionmentioning
confidence: 90%
“…One likely pathway by which parental anxiety may contribute to child BI/anxiety is through heredity, given previous work showing modest‐to‐high levels of heritability in the traits of BI and social anxiety (Eley et al., 2015; Smith et al., 2012). However, parents with anxiety may also contribute to the development of children's BI or anxiety by shaping their prenatal (Buss et al., 2012) and/or socialization experiences (Rickman & Davidson, 1994; Zeytinoglu et al., 2022).…”
Section: The Role Of Caregiving In the Relation Between Behavioral In...mentioning
confidence: 99%
“…Some researchers have suggested that because different types of anxiety are highly comorbid, their differences are not clinically meaningful (Rutter, 2011). On the other hand, other researchers have highlighted the importance of the differences between types of anxiety (Pine, 2007(Pine, , 2011 because they show differences in emotion processing and responding (Blair et al, 2008;Kessel et al, 2015;Mennin et al, 2009;Salum et al, 2013)-which might ultimately lead to differential outcomes (e.g., Zeytinoglu, Neuman, et al, 2021). In this way, by using the pandemic and its associated restrictions as a natural experiment, we were able to examine whether different types of anxiety predicted different outcomes, informing theoretical discussions of anxiety-disorder research.…”
Section: Special Issue Articlementioning
confidence: 99%